For an Animistic Camera: A Symbiotic Manifesto for Sensory and Affective Documentary - Alvarez Astacio, Patricia (2018)
This article plays with the format of the artist manifesto in order to propose a new understanding about the relationship between body and camera in contemporary sensory and affective documentary. The stories we tell ourselves about technology influence how we use it, the narratives we create with it, and how we produce meaning in film. Following the call to develop new perspectives in our Anthropocenic times that will allow us to narrate new stories about ourselves and our others (humans, non-humans, more-than-humans) and to the need of imagining new futures beyond capitalism; this manifesto emphasizes the importance of re-conceptualizing the understanding of the relationship we have with the mechanical body of the camera. Here, I propose to see this interaction of bodies from an animistic or symbiotic perspective, where technology is not just a disposable tool destined to exclusively reproduce a human will. This animistic or symbiotic camera emerges from a dialogue with earlier proposals that marked key trajectories in the history of documentary and ethnographic cinema. The manifestos of Dziga Vertov, Jean Rouch and Maya Deren formulate a relationship between a body and an active camera, that is alive, has a soul, and allows us to tell stories about complex sensible worlds beyond sight. Their proposals present a critical vision of a relationship to technology necessary to create new representations about reality that can responds to changing socio-political contexts. We seek to promote and re-think the production of a documentary cinema that emerges from our interaction with a vibrant camera, generated and generative, to develop narratives that embody us and evoke the intuitive, flexible and porous reality of the world we live in.